Иодометрическое определние глюкозы с использованием твердофазной экстракции иода в полиметакрилатную матрицу - Баженова, Ольга Александровна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
Glucose determination is one of the most popular types of analysis, since glucose is one of the most important indicators of human health. We have proposed a solid-phase spectrophotometric technique based on the reaction of glucose oxidation with the formation of gluconic acid and hydrogen peroxide under the catalytic action of glucose oxidase. To determine the hydrogen peroxide formed, we proposed to use its reaction of interaction with iodides in solution to form iodine with its subsequent solid-phase extraction in PMM or in PMM-Au0.